A Differential Game with Investment in Transport and Communication R&D - Luca Colombo; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
In this paper we propose a simple, intuitive approach to asset valuation in terms of marginal contributions to the characteristics (moments) of the market portfolio. Considering only the first two moments, mean and variance, the valuation equation is shown to correspond to Sharpe's CAPM. A risk-neutral pricing formula is easily derived, showing the equivalence between CAPM and the Black and Scholes' model. Extensions to higher moments like skewness and kurtosis are straightforward, providing a generalized valuation equation. Finally, the generalized equation is derived in a different, more rigorous way, as a result of a classical intertemporal general equilibrium model.
Keywords: 330